Synthesis, properties and applications of graphene doped with boron, nitrogen and other elements - Rao, C.N.R.; Gopalakrishnan, K.; Govindaraj, A. (Nano today, 2014)
•Graphene can be doped with nitrogen, boron and other elements.•Chemically doped graphenes have many novel properties.•N-doped graphene can be used in photochemical water splitting and in oxygen reduction reaction.•N-doped graphene shows excellent performance in supercapacitors and in Li batteries.•Field emission properties of doped graphene are noteworthy. Chemical doping of graphene becomes necessary to create a band gap which is useful for various applications. Furthermore, chemical doping of elements like boron and nitrogen in graphene gives rise to useful properties. Since chemically doped graphene is both of academic and technical importance, we have prepared this article on the present status of various aspects of this important class of materials. In doing so, we have covered the recent literature on this subject citing all the major references. Some of the aspects that we have covered are the synthesis of chemically doped graphene followed by properties and applications. The applications discussed relate to gas adsorption, lithium batteries, supercapacitors, oxygen reduction reaction, field emission and photochemical water splitting. Characterization of chemically doped graphene also included. We believe that the article will be useful to all those interested in graphene and related materials and provides the present status of the subject.